Population Pharmacokinetics of Fruquintinib, a Selective Oral Inhibitor of VEGFR ‐1, ‐2, and ‐3, in Patients with Refractory Metastatic Colorectal Cancer - Zhou, Xiaofei; Yang, Xiaoyan; Grinshpun, Boris; Taylor, Adekemi; Strong, Laura; Dasari, Arvind; Wang‐Gillam, Andrea; Li, Jin; Xu, Rui‐Hua; Gupta, Neeraj; Chien, Caly (Journal of clinical pharmacology, 2025)
Fruquintinib is a selective, oral tyrosine kinase inhibitor of all three vascular endothelial growth factor receptors 1, 2, and 3, which is approved for patients with previously treated metastatic colorectal cancer regardless of biomarker status. This population pharmacokinetic (PK) analysis characterized sources of interpatient variability on the PK of fruquintinib and its major metabolite M11 using data from 557 subjects who received fruquintinib in five phase I/Ib studies and the FRESCO‐2 phase III study. The integrated model was a one‐compartment model with first‐order absorption, lag time in absorption, and linear elimination for fruquintinib and a one‐compartment model with linear elimination for M11. The half‐life of fruquintinib and M11 were estimated to be 43.2 and 54 h, respectively. Fruquintinib PK demonstrated dose proportionality. Fruquintinib oral clearance and apparent volume of distribution (V/F) increased with increasing body weight. Fruquintinib absorption rate constant was 60.7% lower with concurrent use of proton‐pump inhibitors (PPIs), and fruquintinib V/F was 9.08% lower in healthy subjects versus patients with cancer. Magnitudes of the covariate effects of body weight, concurrent use of PPIs, and health status on fruquintinib exposures were estimated to be <20%, which is not considered clinically meaningful. Age (18.0‐82.0 years), sex, race (Asian, Black, and White), ethnicity (Hispanic vs non‐Hispanic), Eastern Cooperative Oncology Group performance status score, tumor type, mild or moderate renal impairment, and mild hepatic impairment had no clinically meaningful impact on fruquintinib or M11 PK. This analysis supports the same fruquintinib starting dosage, without need for adjustments, for these patient‐specific factors.